2014
DOI: 10.3233/ies-140549
|View full text |Cite
|
Sign up to set email alerts
|

Cyclists and triathletes do not differ in muscle volume, muscle recruitment or pedal force effectiveness

Abstract: BACKGROUND: Non-specific adaptation from training can elicit similar muscle volume and muscle activation between cyclists and triathletes which differ in comparison to non-athletes. OBJECTIVE: To compare muscle volume, muscle activation and pedal forces of cyclists, triathletes and non-athletes. METHODS: Twelve cyclists, ten triathletes and twelve non-athletes performed an incremental test to determine their maximal power output (POMAX). Quadriceps and triceps surae volume were estimated from ultrasound images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is suggested that future studies should split the pedal revolution into separate power and recovery phases. This approach has been adopted previously [32] and has, at times, been extended to an even more detailed analysis of four "quarters" across the pedal revolution [33][34][35]. The purpose of such a split would be to effectively separate the power and recovery phases from the areas at the top and bottom of the pedal revolution, which have long been identified as areas where pedalling kinematics are altered due to tangential force being at a minimum [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that future studies should split the pedal revolution into separate power and recovery phases. This approach has been adopted previously [32] and has, at times, been extended to an even more detailed analysis of four "quarters" across the pedal revolution [33][34][35]. The purpose of such a split would be to effectively separate the power and recovery phases from the areas at the top and bottom of the pedal revolution, which have long been identified as areas where pedalling kinematics are altered due to tangential force being at a minimum [36,37].…”
Section: Discussionmentioning
confidence: 99%